Selecting managers in the chemical and chemical products industry in Malaysia - Mustafa, Munauwar; Ghazali, Zahiruddin; Kassim, Mohd Shah; Hasan, Hasnizam (2000)
The main objectives of this study are to describe the current selection practices to select managers according to ownership types and sizes in the chemical and chemical products industry in Malaysia. The population for this research consisted of 242 companies in the chemical and chemical products industry listed in the 1998 directory provided by MIDA (Malaysian Industrial Development Agency). By using the simple random sampling method, 152 companies were chosen as samples. The data were collected by means of mail questionnaire. Of the 152 questionnaires mailed, 22 came back indicating that either the companies were closed down or had moved to a new address.Minus the undelivered mails, the final result was that only 30 questionnaires were received representing 23.07 percent response rate.This study shows that the most frequently used methods to select mangers in the chemical and chemical products companies in descending order are preliminary or screening interview, application forms or blanks, reference checks, structured employment interview, letters of recommendation and personality tests.This study also reveals that structured employment interview is used more frequently than the unstructured interview; about half of the companies did not used the unstructured interview at all selection managers.Other than personality tests, non-traditional selection methods such as assessment center, honesty tests, psychological tests and drug tests are not used by majority of the companies.However, the score for these methods can be considered moderate as one forth of the respondents do use them often.It is believed that each selection effort consists of more than one method; each of these methods is used to complement each other.Normally, companies maintain some records to examine some records to examine the efficiency of each selection method used.However, in our case only 26.7 percent of the organizations do maintain a record on time-lapse data i.e the average time that elapses between points of decision making for each selection methods used and only 20.7 percent of the organizations do maintain a record on yield ratio i.e the ratio of applicants to hires at each step in the selection process.It is quite safe to say that the usage of the selection methods was based on the human resource managers' perceptions and was not based on any empirical evidence.These findings expose a major weakness in the practice of selection among the chemical and chemical products companies in Malaysia because without these data.It is very hard for any practitioners to do the human resource planning and staffing effectively and efficiently.